Etymologies of Brazilian Amphibians - Lavilla, Esteban O.; Caramaschi, Ulisses; Langone, José Antônio; Baêta, Délio (Herpetologia Brasileira, 2026)
The etymologies of the generic names and specific epithets of 1,206 Brazilian amphibian species and their synonyms, are presented. The compilation ranges from Rana pipa, the first Brazilian species described in the 10th edition of the Systema Naturae by Linnaeus (1758), to Osteocephalus melanops, published by Melo-Sampaio et al. on December 20, 2021. Within this range are 18 species named in the XVIII century, followed by 204 in the XIX, 527 in the XX, and 457 in the first 21 years of the XXIth century. A total of 1,706 primary quotations are listed, representing a much larger number if the referred desinenes and variations of a same name were considered.